DIGITALISATION OF ACCOUNTING AS AN INTEGRAL PART OF THE DEVELOPMENT OF THE DIGITAL ECONOMY IN UKRAINE - Дмитренко, Алла; Кравченко, Олена (SWorldJournal, 2026)
Today, many companies use specialized accounting software. These are not just computerized versions of old journals, but powerful systems that can independently process data, find errors and even give advice. Today, digitalization is driven by the rapid